Effect of Kelulut Honey Nanoparticles Coating on the Changes of Respiration Rate, Ascorbic Acid, and Total Phenolic Content of Papaya (Carica papayaL.) during Cold Storage - Bernard, Maringgal; Norhashila, Hashim; Intan Syafinaz, Mohamed Amin Tawakkal; Mahmud, Tengku Muda Mohamed; Muhammad Hazwan, Hamzah; Maimunah, Mohd Ali (MDPI, 2021)
This study evaluated the respiration rate of coated and uncoated (control) papayas(Carica papayaL.) with 15% ofKeluluthoney (KH) nanoparticles (Nps) coating solution during coldstorage at 12±1◦C for 21 days. The respiration rate of the papayas significantly changed duringstorage, with an increase in CO2and a decrease in O2and C2H4, while the ascorbic acid and totalphenolic content was maintained. The changes in respiration rate were rather slower for coatedpapayas when compared to control ones. A kinetic model was established from the experimentaldata to describe the changes of O2, CO2, and C2H4production in papayas throughout the storageperiod. All O2, CO2, and C2H4were experimentally retrieved from a closed system method and thenrepresented by the Peleg model. The outcomes indicated the Peleg constantK1andK2, which weregained from linear regression analysis and coefficients of determination (R2), seemed to fit well withthe experimental data, whereby theR2values exceeded 0.85 for both coated and control papayas. Themodel confirmed both the capability and predictability aspects of the respiration rate displayed bypapayas coated with KH Nps throughout the cold storage period. This is supported by the differencesin the stomatal aperture of coated and control papaya shown by microstructural images.